2016
DOI: 10.1080/19443994.2016.1189697
|View full text |Cite
|
Sign up to set email alerts
|

Use of concentrate water from seawater desalination plant as magnesium sources for struvite formation by using anaerobically digested effluent of swine wastewater

Abstract: Young Park (2016): Use of concentrate water from seawater desalination plant as magnesium sources for struvite formation by using anaerobically digested effluent of swine wastewater, Desalination and Water Treatment, A B S T R A C TAlthough struvite crystallization has been proven an effective process to recover nutrients from wastewater, this method has not been used widely because of the cost of the raw chemicals, such as magnesium chloride, required as supplements. In this study, in view of the high cost of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The presence of nondiscrete dissolved organic matter (DOM) in LWE is known to hinder the struvite formation process, which is commonly carried out at optimal pH 9–10. Several approaches are known to mitigate these hindrances to struvite recovery from LWE through DOM removal from the dissolved phase by flocculation, , osmosis/filtration, , and digestion. , In contrast to hindrance from non-descript DOM such as humic substances to struvite growth, ,, negatively charged low molecular weight (LMW) organics such as phenols and carboxylic acids promoted nucleation and growth of struvite in simulated LWE. , Additional research found that adding a negatively charged soluble short peptide labeled shADP5 (short human-derived amelogenin-derived peptide 5, 1736.8 g mol –1 ) to simulated wastewater (SWW) also increased the struvite precipitation rate. This study evaluated the relationship between the ionic charge of the dissolved LMW organics benzylamine, benzoate, and toluene to struvite growth rates and morphology in SWW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of nondiscrete dissolved organic matter (DOM) in LWE is known to hinder the struvite formation process, which is commonly carried out at optimal pH 9–10. Several approaches are known to mitigate these hindrances to struvite recovery from LWE through DOM removal from the dissolved phase by flocculation, , osmosis/filtration, , and digestion. , In contrast to hindrance from non-descript DOM such as humic substances to struvite growth, ,, negatively charged low molecular weight (LMW) organics such as phenols and carboxylic acids promoted nucleation and growth of struvite in simulated LWE. , Additional research found that adding a negatively charged soluble short peptide labeled shADP5 (short human-derived amelogenin-derived peptide 5, 1736.8 g mol –1 ) to simulated wastewater (SWW) also increased the struvite precipitation rate. This study evaluated the relationship between the ionic charge of the dissolved LMW organics benzylamine, benzoate, and toluene to struvite growth rates and morphology in SWW.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The presence of nondiscrete dissolved organic matter (DOM) in LWE is known to hinder the struvite formation process, which is commonly carried out at optimal pH 9− 10. 18−22 Several approaches are known to mitigate these hindrances to struvite recovery from LWE through DOM removal from the dissolved phase by flocculation, 23,24 osmosis/ filtration, 25,26 and digestion. 27,28 In contrast to hindrance from non-descript DOM such as humic substances to struvite growth, 13,18,29 negatively charged low molecular weight (LMW) organics such as phenols and carboxylic acids promoted nucleation and growth of struvite in simulated LWE.…”
Section: Introductionmentioning
confidence: 99%